The Digital Sentinel: AI Fraud Detection vs. Traditional Audits in the Age of Digital Health - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
Healthcare fraud is a pervasive global challenge, costing billions annually and diverting critical resources from patient care. As the healthcare industry ra...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Patient Care; Machine Learning